2020
DOI: 10.1002/cncr.33386
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in hospitalized patients with cancer and coronavirus disease 2019: A systematic review and meta‐analysis of cohort studies

Abstract: Background Heterogeneous evidence exists on the effect of coronavirus disease 2019 (COVID‐19) on the clinical outcomes of patients with cancer. Methods A systematic review was performed using the Medline, Embase, and CENTRAL databases and the World Health Organization Novel Coronavirus website to identify studies that reported mortality and characteristics of patients with cancer who were diagnosed with COVID‐19. The primary study outcome was mortality, defined as all‐cause mortality or in‐hospital mortality w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
99
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 45 publications
5
99
1
4
Order By: Relevance
“…Patients participating in clinical trials often have progressive advanced-stage cancer, are undergoing active treatment and usually make several visits to clinics and hospitals for study-related procedures, which potentially increases their exposure to SARS-CoV-2 infection at multiple points. Thus, prioritization for vaccination is imperative, particularly considering that patients with cancer also seem to have an increased risk of severe COVID-19 and complications and mortality from the disease [7][8][9][10][11][12][13][14] . Due consideration should also be given to other well-recognized risk factors for severe COVID-19, such as advanced age (≥65 years), comorbidities (for example, chronic pulmonary, cardiovascular or renal disease) and other sociodemographic factors (such as overcrowded housing, single-parent households and ethnicity) 29 , when prioritizing patients with cancer for vaccination, with priority given to those at most risk.…”
Section: Classification Of Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients participating in clinical trials often have progressive advanced-stage cancer, are undergoing active treatment and usually make several visits to clinics and hospitals for study-related procedures, which potentially increases their exposure to SARS-CoV-2 infection at multiple points. Thus, prioritization for vaccination is imperative, particularly considering that patients with cancer also seem to have an increased risk of severe COVID-19 and complications and mortality from the disease [7][8][9][10][11][12][13][14] . Due consideration should also be given to other well-recognized risk factors for severe COVID-19, such as advanced age (≥65 years), comorbidities (for example, chronic pulmonary, cardiovascular or renal disease) and other sociodemographic factors (such as overcrowded housing, single-parent households and ethnicity) 29 , when prioritizing patients with cancer for vaccination, with priority given to those at most risk.…”
Section: Classification Of Vaccinesmentioning
confidence: 99%
“…Multiple studies have revealed that patients with cancer have an increased risk of complications and mortality from COVID-19, including 30-day mortality of 30% in hospitalized patients with COVID-19 and cancer compared with 21% in those without cancer [7][8][9][10][11][12][13][14] . Given the greater severity of the disease and higher risk of death, patients with cancer are considered a high-priority subgroup for COVID-19 vaccination.…”
mentioning
confidence: 99%
“…According to the known current evidence, mortality rates for cancer patients with concomitant COVID-19 are significantly higher than in the general COVID-19 population, and are associated with increased age, male gender and prior conditions [92,93]. The mortality rates published so far vary widely [94 -96].…”
Section: Breast Cancer During the Covid-19 Pandemicmentioning
confidence: 99%
“…Currently, mortality rates of cancer patients with COVID-19 are much higher at 25-30 % [92,93]. A meta-analysis of cohort studies of mortality in patients hospitalised for cancer and COVID-19 found a pooled 30-day mortality rate of 30 % (95 % CI: 25-35 %), with a rate of 26% (95% CI: 22-31 %) for the subgroup with solid tumours [93]. However, it should be noted that meta-analysis included mostly inpatient cases and that the cohorts came from different health care systems.…”
Section: Breast Cancer During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation